ANALYSIS OF CLINICAL DIAGNOSTIC METHODS FOR DISEASES PRESENTING WITH VESTIBULAR DISORDERS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Benign paroxysmal positional vertigo (BPPV) and vestibular migraine are among the most common vestibular pathologies that present with dizziness. Due to their similar clinical symptoms, differential diagnosis is of critical importance. This prospective study evaluated the effectiveness of clinical and instrumental methods for diagnosing BPPV and vestibular migraine in 196 patients. All patients underwent a clinical-neurological examination, the Dix-Hallpike test, the supine roll test, the Head Impulse Test, videonystagmography (VNG), video Head Impulse Test (vHIT), vestibular evoked myogenic potentials (VEMP), and audiometry. Of the 196 patients, 104 (53.1%) were diagnosed with BPPV, and 92 (46.9%) were diagnosed with vestibular migraine. The sensitivity of the Dix-Hallpike test for BPPV was 93.2%, and its specificity was 90.4%. The diagnostic accuracy of a comprehensive assessment based on clinical criteria for identifying vestibular migraine was 88.6%. The results of the study demonstrated that a systematic clinical algorithm is highly effective in differentiating between BPPV and vestibular migraine.